THE EFFECT OF APPLYING CONTEXTUAL LEARNING TO SCIENTIFIC ATTITUDE ON ECOSYSTEM MATERIAL - Jhon Riswanda; Tutut Handayani; Muhammad Isnaini; Listina Sekar Taufiqa (Al 'Ilmi : Jurnal Pendidikan MIPA, 2017)
Contextual teaching and learning (CTL) is a conception that helps the teacher link the subject content to realworldsituations and motivate students to make connections between knowledge and application in their lives.This study aims to describe the effect of applying contextual learning model to the scientific attitude of juniorhigh school students on ecosystem material. This research is quasi experiment and uses the Matching OnlyPosttest-Only Control Group Design. The implementation of this study include of 33 students as experimentalclass and 32 students as control class in one of junior high school at East OKU. The research instrument used inin the form of rubric assessment, questionnaire, and observation sheet. Data was analyzed by using MicrosoftExcel and SPSS program 16. The statically result showed that contextual learning model had an effect onimproving students ’scientific attitude so that they could reach the minimum criteria. This is because the studentcan learn the lesson material presented through the context of their lives, and find meaning during the learningprocess, so that learning will become more meaningful and fun with the ecosystem material. This learningmodel can improve students’ scientific attitude through the syntax contained in it. Keywords: CTL learning model, scientific attitude